PENGARUH BELANJA MODAL, TENAGA KERJA DAN PAD TERHADAP PDRB PROVINSI JAWA TENGAH - Humaidi Hakim; M.Faisal Abdullah; Arfida Boedirochminarni (Jurnal Ilmu Ekonomi JIE, 2019)
This research is aimed at finding out the influence of capital expenditure, labor and authentic local income on gross regional domestic product Cities/Regencies Province Central Java. In this research, the researcher used multiple regression as the research instrument with panel data during the period of six years in 2013-2018. This research is showed that the variable of capital expenditure, labor and authentic local income influence on variable Gross Regional Domestic Product, increasing variable capital expenditure, labor and authentic local income then the amount of production goods and services will increase thereby tringgering an increase in the amount Gross Regional Domestic Product. This research used Fixed Effect Model as the research design. Based on the result of data analysis, it showed that the variable of capital expenditure positively and significantly local income on gross regional domestic product, variable of labor positively and significantly local income on gross regional domestic product, variable of authentic local income positively and significantly local income on gross regional domestic product.